Pengaruh Pemberian Minuman Kombinasi Jahe dan Lemon untuk Mengurangi Emesis Gravidarum Pada Ibu Hamil Trimester I di Puskesmas Pebayuran - Tahun, Omega Dr; Husnulaini, Kamah (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Emesis Gravidarum is a condition of nausea and vomiting that occurs in early pregnancy, especially in the first four weeks, and usually decreases at twelve weeks of gestation. Although often accompanied by vomiting, the frequency is no more than five times a day. According to the World Health Organization, around 14% of pregnant women in the world experience this condition. In Indonesia, in 2021, the prevalence reached 67.9%, while in West Java Province, 13% of pregnant women experienced nausea and vomiting. This condition is often experienced by primigravida (80%) and multigravida (60%) pregnant women, so proper treatment is needed. To determine the effect of giving a combination of ginger and lemon drinks to reduce Emesis Gravidarum in pregnant women in the first trimester at the Pebayuran Health Center in 2024. Using a quantitative research type with a pre-experimental design using One Group Pretest-Posttest Design. The sample used was 30 pregnant women using the total sampling technique, and data analysis was carried out using the Wilcoxon Range List test to test the differences before and after giving a combination of ginger and lemon drinks. Shows a P value <0.001, which means there is a significant effect between giving a combination of ginger and lemon drinks on reducing Emesis Gravidarum in pregnant women in the first trimester. There is an effect of giving a combination of ginger and lemon drinks to reduce Emesis Gravidarum in pregnant women in the first trimester at the Pebayuran Health Center in 2024. It is hoped that these findings can provide an effective alternative therapy in reducing symptoms of nausea and vomiting in pregnant women and can be implemented by health institutions and the community as an additional solution in dealing with Emesis Gravidarum. Keywords: Emesis Gravidarum, Combination of Ginger and Lemon Drinks  ABSTRAK Emesis Gravidarum adalah kondisi mual muntah yang terjadi pada awal kehamilan, terutama pada empat minggu pertama, dan biasanya berkurang pada usia kehamilan dua belas minggu. Meskipun sering disertai muntah, frekuensinya tidak lebih dari lima kali sehari. Menurut World Health Organization, sekitar 14% wanita hamil di dunia mengalami kondisi ini. Di Indonesia, pada tahun 2021, prevalensi mencapai 67,9%, sedangkan di Provinsi Jawa Barat tercatat 13% ibu hamil mengalami mual muntah. Kondisi ini banyak dialami oleh ibu hamil primigravida (80%) dan multigravida (60%), sehingga penanganan yang tepat sangat diperlukan. Mengetahui pengaruh pemberian minuman kombinasi jahe dan lemon untuk mengurangi Emesis Gravidarum pada ibu hamil trimester I di Puskesmas Pebayuran tahun 2024. Menggunakan jenis penelitian kuantitatif dengan desain pra-eksperimen menggunakan One Group Pretest-Posttest Design. Sampel yang digunakan sebanyak 30 ibu hamil menggunakan tehnik total sampling, dan analisis data dilakukan dengan uji Wilcoxon Range List untuk menguji perbedaan sebelum dan sesudah pemberian minuman kombinasi jahe dan lemon. Menunjukkan nilai P < 0.001, yang berarti terdapat pengaruh signifikan antara pemberian minuman kombinasi jahe dan lemon terhadap pengurangan Emesis Gravidarum pada ibu hamil trimester I. Terdapat pengaruh pemberian minuman kombinasi jahe dan lemon untuk mengurangi Emesis Gravidarum pada ibu hamil trimester I di Puskesmas Pebayuran tahun 2024. Diharapkan temuan ini dapat memberikan alternatif terapi yang efektif dalam mengurangi gejala mual muntah pada ibu hamil dan dapat diimplementasikan oleh institusi kesehatan serta masyarakat sebagai solusi tambahan dalam menangani Emesis Gravidarum. Kata Kunci: Emesis Gravidarum, Minuman Kombinasi Jahe dan Lemon